Sustainable Use of Land and Water Resoruces in Regional Master Socio-economic Development Planning for the Mekong Delta under the Context of Vietnam Integration into Global Economics - Dong, Hoang Sy; Phuong, Nguyen Van; Vinh, Nguyen Quanh; Vinh, Trinh Quang (World Bank, Washington, DC, 2013)
This report directly provide recommendations for improvement of the quality of the regional master socio-econsomic development plan and national laud use plans for Vietnam, to the year 2020. It provides analysis and assessment of the reviewed-adjusted-ammended socio-economic development plan for the Mekong Delta, which is aimed at improvement of the quality and feasibility of regional socio-economic development plans for the industrialization, modernization and integration of Vietnam into the global economic market. Land and water resources were evaluated, case studies were compiled on export commodity production models with consideration of the potential as commodities.